Síntese e caracterização da hidroxiapatita pelo método de precipitação por via úmida com reações de ácido-base - GONÇALVES, Camilly Peres (2021)
The main advance in the area of biomaterials has occurred in several countries due to the increase of the population and, consequently, of its life expectancy and quality. As a result, diseases related to bone loss, such as osteoporosis, are gaining prominence, and thus the demand for biomaterials that are compatible with the human body is increasing. Calcium phosphate ceramics have stood out among the so-called bioceramics, for presenting lower rates of rejection when they come into contact with human tissue. The hydroxyapatite is the most used bioceramic lately in the medical area due to its high bioactivity, and there are several methods to obtain it, making it to reach several properties in order to adapt in the best way to where it will be used. Thus, the objective of this study was to produce and microstructurally characterize hydroxyapatite in dilution molarities of phosphoric acid and ammonium hydroxide in 0.5, 1.0 and 1.5 molar, having as calcium precursor the synthetic calcium hydroxide, using the precipitation technique by wet method, by acid-base reaction for the synthesis of HA. The material obtained was calcined at a temperature of 900°C. The powder obtained was characterized by DRX, FTIR, MEV and EDS. The method allowed obtaining structured calcium phosphate powder from which hydroxyapatite was obtained. During the characterization process, it was possible to observe in the DRX analyses that all samples showed good crystallinity, but samples synthesized at 1.0 and 1.5 molar presented more intense and narrower peaks compared to the sample synthesized at 0.5 molar, suggesting that the concentration interferes in the grain formation. It was also possible to observe in the FTIR analyses the presence of bands that characterize the HA phase, showing PO43- and OH groupings at higher intensity and CO32- and H2O at lower intensity. It was also possible to observe in the MEV images, agglomerated HA particles in all samples, however, samples synthesized at 0.5 and 1.5 molar showed more dispersed particles and with crystallites of relatively smaller sizes compared to the sample synthesized at 1.0 molar suggesting that molarity also interferes in the production of grains. Thus, the wet synthesis method, with acid-base reaction, in dilution molarities of phosphoric acid and ammonium hydroxide in 0.5, 1.0 and 1.5 molar, at 900ºC of calcination, was satisfactory to obtain hydroxyapatite (HA).